PENERAPAN ROCKET STOVE SEBAGAI SOLUSI RAMAH LINGKUNGAN DALAM PEMBAKARAN SAMPAH DI DESA MEKARWANGI - Ramadhan , Devan; Tirtoaji, Mahes Okta; Ferdinansyah, Rafly; Firdaus, Surya; Adi Candra, Ray Abdul Somad; Fadilah, Dilla Nurul; Sunendang, Novi Fitriani; Jamila, Maryam; Sari, Webi Dwi; Kartini, Titin (Batara Wisnu : Indonesian Journal of Community Services, 2025)
In Mekarwangi Village, Pagaden Barat Subdistrict, Subang Regency, the University of Subang's Student Community Service Program (KKNM) focuses on the use of rocket stove technology for waste management. The high volume of household waste and traditional burning methods that produce excessive smoke, which negatively impact the environment, are the main challenges faced by the community. The use of rocket stoves as appropriate technology can reduce smoke production, improve combustion efficiency, and be more environmentally friendly. The program utilizes socialization, demonstrations, and community involvement in the use of rocket stoves. Thus, rocket stoves have proven to be an effective alternative for waste burning while also serving as a tool for community empowerment to create a cleaner and healthier village environment. The results of the activities also show that the community has a better understanding of how to manage waste in a healthy and environmentally friendly manner and is more active in applying this technology.